1991
DOI: 10.1085/jgp.98.4.815
|View full text |Cite
|
Sign up to set email alerts
|

Apparent affinity of the Na/K pump for ouabain in cultured chick cardiac myocytes. Effects of Nai and Ko.

Abstract: The measured apparent affinity (K0.5) of the Na/K pump for ouabain has been reported to vary over a wide range. In a previous report we found that changing Na~ could alter apparent affinity by at least an order of magnitude and that the model presented predicted this variability. To increase our understanding of this variability, isolated cells or two-to three-cell clusters of cardiac myocytes from 11-d embryonic chick were used to measure the effects of Na~ and K o on the K05 of the Na/K pump for ouabain. Myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1

Year Published

1992
1992
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 31 publications
2
13
1
Order By: Relevance
“…To analyse our data further a six-state cyclic model of the Na¤-K¤ pump was used (Chapman, Johnson & Kootsey, 1983;Stimers, Liu & Lieberman, 1991). In the present work the only modification of the model was to include voltage dependence on the rate constants f× and b× for the Na¤ translocation step.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyse our data further a six-state cyclic model of the Na¤-K¤ pump was used (Chapman, Johnson & Kootsey, 1983;Stimers, Liu & Lieberman, 1991). In the present work the only modification of the model was to include voltage dependence on the rate constants f× and b× for the Na¤ translocation step.…”
Section: Modelmentioning
confidence: 99%
“…Additionally, each of the other rate constants were varied to determine if changes in any other rate constants might yield simulations that are consistent with the results of our present and previous work. Table 1 lists initial parameters obtained from previous reports in the literature (Chapman et al 1983;Stimers et al 1991). To determine if this model could predict an increase in Na¤-K¤ pump current observed at 0 mÒ K¸without changing voltage dependence (see previous section) we varied sequentially forward and backward rate constants with indices: 2, 3, 5 and 6.…”
Section: Voltage Dependence Of Ipmentioning
confidence: 99%
“…Previous studies have demonstrated that activation of adenosine receptors in these cultured heart cells produces physiologic effects similar to those elicited by adenosine in the adult mammalian heart (25)(26)(27)(28). The cultured ventricular myocytes contain predominantly ( Ͼ 90%) myocytes (21; our unpublished data) and are largely devoid of neuronal, blood, or vascular cells, thus the confounding influence of changes in blood flow is avoided (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). The present study aims to develop the chick ventricular cell culture as a model to investigate the role of adenosine receptor subtypes in the preconditioning process and to study the mechanism(s) by which preconditioning of the ventricular myocytes can be modulated.…”
Section: Introductionmentioning
confidence: 99%
“…Ventricular myocytes cultured from chick embryos retain many of the properties of the intact heart and have served as a useful model for a variety of experimental paradigms (18)(19)(20)(21)(22)(23)(24). Previous studies have demonstrated that activation of adenosine receptors in these cultured heart cells produces physiologic effects similar to those elicited by adenosine in the adult mammalian heart (25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…N. Hermanrs, H. G. Glitsch and F Verdonck voltage clamp measurements (Stimers, Lobaugh, Liu, Shigeto & Lieberman, 1990) and whole-cell recording (Hainill, Alarty, Neher, Sakmann & Sigworth, 1981) [Na+]i (Stimers, Liu & Lieberman, 1991;Bielen, Glitsch & Verdonck, 1992 [K+]o and tlhus a decrease in the apparent affinitv of the Na+-K+ pump for the drugs (Stimers et al 1991;Bielen et al 1992). According to the latter authors the antagonistic effect of K+ on the inhibition of Ip by dilhydro-ouabain (DHO) in rabbit Purkinje cells is almost entirely due to a reduction of the apparent DHO association rate constant, w7hich is in agreement with an earlier study on a multicellular guinea-pig ventricular preparation (Daut, 1983).…”
mentioning
confidence: 99%